Climate Change and Global Challenges - Shrivastava, Umesh Prasad (International Journal of Social Sciences and Management, 2014)
No Abstract DOI: http://dx.doi.org/10.3126/ijssm.v1i3.10765 Int. J. Soc. Sci. Manage. Vol.1(3) 2014: 86-87